THE IMPACT OF DIGITAL LITERACY ON ENGLISH LANGUAGE LEARNING IN MODERN EDUCATIONAL CONTEXTS - Saidova Moxigul; Gʻaybullayeva X.M. (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This paper examines the growing significance of digital literacy in English language learning within contemporary educational environments. It explores theoretical perspectives, digital competencies, technology-based instruction models, and the integration of multimedia tools in ELT classrooms. The study analyzes how digital platforms, online communication, multimodal input, and artificial intelligence contribute to learners’ language development. Findings indicate that digital literacy enhances learner motivation, autonomy, multimodal comprehension, 21st-century competencies, and access to authentic language input. The article concludes with methodological recommendations for teachers and curriculum developers to foster digital literacy as a core component of modern ELT pedagogy.